An experimental evaluation of organic rankine cycle using HCFC-141b as a working fluid - Saiai P. (2017)
© Research India Publications. An organic Rankine cycle (ORC) using HCFC-141b (1,1-Dichloro-1-fluoroethane) as a working fluid were experimental studied for an electricity generation. The system performance and efficiency evaluation under the low pressure and low temperature heat source have been analyzed. The system model is built by interconnecting different sub-models, the heat exchanger models, a high pressure pump model and an impulse radial turbine model. Measured performance of the system prototype is presented and used to validate the theoretical calculations. Several variations were investigated in order that determine the system performance and efficiency for convert the mechanical work to electicity from the system. This model is finally used to investigate potential improvements of the prototype.